The Meaning of the Word “Wazir” in the Qur’an: A Semantic Analysis - Nur Rochim, Mohammad Rizal; Nugroho, Kharis; Nirwana, Andri (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
The purpose of this study is to explore and understand the meaning of the word